The daily 5 : fostering literacy independence in the elementary grades - Boushey, Gail, 1956-; Moser, Joan, 1962- (Portland, Me. : Stenhouse, 2006)
Describes the Daily Five literacy program which consists of independent tasks for students and allows elementary teachers more time to meet with small groups or individuals; and provides advice on implementing it in the classroom.
Includes bibliographical references (p. 107-110).
Professional
Keywords: Individualized instruction -- Case studies; Language arts (Elementary); Individualized instruction -- Case studies; Language arts